Risk Factors Analysis of Lime Dust Exposure with ARI Incidence on workers: Study in Limestone Burning Industry Margasari District, Tegal Regency, Central Java - Mirza Fathan Fuadi; Onny Setiani; Yusniar Hanani Darundiati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Limestone burning industrial activities have the potential to cause air pollution in the workplace in the form of lime dust. Limestone burning industry with a high level of limestone dust particles exposure could be risk factor for acute respiratory infections (ARI) on workers. Based on the preliminary study, it was found that 7 out of 10 workers were exposed to ARI felt symptoms such as coughing, shortness of breath, and sneezing during their work activities and supported by data from the Tegal Regency Environmental Service where the dust content around the industrial area exceeded the standard quality of 284 µg/ Nm3. This study aimed to determine risk factors and analyze the relationship between lime dust exposure with the incidence of ARI in limestone burning workers in Margasari District, Tegal Regency, Central Java. This study used an observational method with a cross-sectional approach. The population of this study were 160 respondents with a sample of 60 respondents, were taken random sampling technique. Data analysis in this study used the Chi-Square test. The results of the analysis showed significant variables, namely total dust particulate content (p=0.048), exposure to inhaled dust (p=0.031), working period (p=0.046), and use of personal protective equipment (p=0.034). Variables that were not significant were length of work (p=0.906) and smoking habits (p=0.319). From this study, it can be concluded that respondents with exposure to inhaled dust above NAV (more than 1 mg/m3) high risk of experiencing acute respiratory infections (ARI). To prevent the occurrence of ARI, it is recommended to use complete personal protective equipment during the work process.Kegiatan industri pembakaran batu kapur berpotensi menimbulkan pencemaran udara di tempat kerja berupa debu kapur. Industri pembakaran batu kapur dengan tingkat paparan partikel debu kapur yang tinggi dapat menjadi faktor risiko terjadinya Infeksi Saluran Pernapasan Akut (ISPA) pada pekerja. Berdasarkan studi pendahuluan diperoleh hasil bahwa 7 dari 10 pekerja terkena ISPA dengan gejala seperti batuk-batuk, sesak, dan bersin selama melakukan aktivitas pekerjaanya dan didukung data dari Dinas Lingkungan Hidup Kabupaten Tegal dimana kadar debu di sekitar area industri melebihi baku mutu sebesar 284 µg/Nm3. Penelitian ini bertujuan untuk mengetahui faktor risiko dan menganalisis hubungan antara paparan debu kapur dengan kejadian ISPA pada pekerja pembakaran batu kapurKecamatan Margasari Kabupaten Tegal Jawa Tengah. Penelitian ini menggunakan metode observasional dengan pendekatan cross-sectional. Populasi penelitian ini sebanyak 160 responden dengan jumlah sampel 60 responden, menggunakan teknik random sampling. Analisis data dalam penelitian ini menggunakan uji Chi-Square. Hasil analisis menunjukkan variabel yang bermakna yaitu kadar partikulat debu total (p=0,048), paparan debu terhirup (p=0,031), masa kerja (p=0,046), dan penggunaan APD (p=0,034). Variabel yang tidak bermakna yaitu lama kerja (p=0,906) dan kebiasaan merokok (p=0,319). Dari penelitian ini dapat disimpulkan, bahwa responden yang memiliki paparan debu terhirup diatas NAB (lebih dari 1 mg/m3) berisiko tinggi terkena ganguaan saluran pernapasan akut (ISPA). Untuk mencegah terjadinya ISPA disarankan untuk menggunakan alat pelindung diri secara lengkap saat proses bekerja.